Effectiveness of Progressive Muscle Relaxation on Sleep Quality: A Systematic Review - Farida, Novi; Bakar, Abu; Pratiwi, Ika Nur (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Progressive muscle relaxation (PMR) is a therapeutic technique that involves sequentially tensing and relaxing muscle groups to promote physical and mental relaxation. It is widely used to improve sleep quality, particularly in adults experiencing sleep disturbances. This systematic review aimed to examine the effectiveness of PMR in enhancing sleep quality. A systematic literature search was conducted using four electronic databases—ScienceDirect, Scopus, PubMed, and CINAHL—covering publications from 2017 to 2022. The keywords used were “progressive muscle relaxation” and “sleep quality.” A total of 1,085 articles were initially identified. After applying inclusion and exclusion criteria based on the PICOT framework (Population, Intervention, Comparison, Outcome, and Time), and following a multi-stage screening process, seven studies were included in the final analysis. The included studies consisted of randomized controlled trials (RCTs) and clinical observational studies involving adult participants. The methodological quality of each study was assessed using the Joanna Briggs Institute (JBI) critical appraisal checklist. All seven studies reported statistically significant improvements in sleep quality following the implementation of PMR. However, variations were found in participant characteristics, duration and frequency of the PMR intervention, and the use of adjunct therapies. Progressive muscle relaxation, when performed under professional supervision, is an effective non-pharmacological intervention to improve sleep quality in adults.